Multielemental analysis in vegetable edible oils by inductively coupled plasma mass spectrometry after solubilisation with tetramethylammonium hydroxide - Savio, Marianela (2014)
Trace metals have negative effects on the oxidative stability of edible oils and they are important because of possibility for oils characterisation. A single-step procedure for trace elemental analysis of edible oils is presented. To this aim, a solubilisation with tetramethylammonium hydroxide (TMAH) was assayed prior to inductively coupled plasma mass spectrometry detection. Small amounts of TMAH were used, resulting in high elemental concentrations. This method was applied to edible oils commercially available in Argentine. Elements present in small amounts (Cu, Ge, Mn, Mo, Ni, Sb, Sr, Ti, and V) were determined in olive, corn, almond and sunflower oils. The limits of detection were between 0.004 μg g−1 for Mn and Sr, and 0.32 μg g−1 for Sb. Principal components analysis was used to correlate the content of trace metals with the type of oils. The two first principal components retained 91.6% of the variability of the system. This is a relatively simple and safe procedure, and could be an attractive alternative for quality control, traceability and routine analysis of edible oils.